Pelecypod Polyclave - James A. Duke (Hello World!, 1970)
The word polyclave, meaning polychotomous key, was coined for the window system for information retrieval herein demonstrated. Presently the pelecypod polyclave is a data bank showing which of 300 pelecypod genera are reported to possess the 360 characteristics in the captions of the data cards on the following 36 pages.